2016
DOI: 10.1146/annurev-lawsocsci-110615-085100
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Complicity in International Human Rights Violations

Abstract: Two literatures-business and human rights and transitional justice-can be usefully combined to consider the issue of corporate complicity in past human rights violations in dictatorships and armed conflicts. But although the transitional justice literature emphasizes the positive role that international pressure plays in advancing justice, the business and human rights literature identifies international constraints in the area of corporate abuses. These include the lack of settled law establishing businesses'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The economic logic or political economy of disappearance refers the economic events linked with the disappearances. As recent studies on corporate responsibility for human rights violations in Colombia and Argentina during the last military dictatorship have shown (Payne and Pereira 2016), the economic interests of companies operated in collaboration with the state authorities to disappear union leaders and even hosted detention centres in corporate facilities during the military dictatorships of the Southern Cone and the Colombian armed conflict. In other words, even when the main purpose of disappearing people during military dictatorships was to eliminate political opponents, in some cases these political opponents were unions leaders or workers whose companies were abetting, allowing, or encouraging practices of state terrorism against their employees.…”
Section: Analytical Framework: the Violence Regime And Logics Of Disa...mentioning
confidence: 99%
“…The economic logic or political economy of disappearance refers the economic events linked with the disappearances. As recent studies on corporate responsibility for human rights violations in Colombia and Argentina during the last military dictatorship have shown (Payne and Pereira 2016), the economic interests of companies operated in collaboration with the state authorities to disappear union leaders and even hosted detention centres in corporate facilities during the military dictatorships of the Southern Cone and the Colombian armed conflict. In other words, even when the main purpose of disappearing people during military dictatorships was to eliminate political opponents, in some cases these political opponents were unions leaders or workers whose companies were abetting, allowing, or encouraging practices of state terrorism against their employees.…”
Section: Analytical Framework: the Violence Regime And Logics Of Disa...mentioning
confidence: 99%
“…Although seminal for understanding TJ in Brazil, Payne’s reflections are limited to understanding the tolerance on the part of national elites in relation to the opening of the regime. Later, along with Gabriel Pereira, the investigations have been refined—based on the convergence of research methods in the field of business, human rights, and TJ—and revealed some aspects of corporate complicity and problematic accountability (Payne & Pereira, 2016).…”
Section: Background Of the Brazilian Experiencementioning
confidence: 99%
“…Ramasastry (2004) has classified three types of complicity (direct corporate complicity, in which corporations’ decisions favor participation in human rights abuses, particularly torture, kidnapping, private imprisonment, and murder; indirect or beneficiary corporate complicity, in which a corporation does not itself commit crime but benefits from crime; and silence or inaction in relation to a host government’s human rights violations, in which a corporation’s mere presence in an authoritarian context in itself amounts to violation, referring to its duty to speak out against violations of rights; similar, Clapham, 2006). Paine and Pereira work with a broader perspective: Corporate complicity does not require ideological affinity between corporations and their state or state-like partners, there are many contexts in which corporations defend their actions as a result of extreme pressure rather than willful collaboration (Payne & Pereira, 2016; similar, Kauzlarich, 2003).…”
Section: Corporate Accountability and Corporate Complicitymentioning
confidence: 99%
“…Although some civilians have been prosecuted, members of the armed forces predominate on the stand. Moreover, while civilian prosecutions have included church figures, doctors, judges and individual businesspeople, the role of business per se in collaborating with grave human rights violations remains a challenge for criminal justice in particular, and transitional justice in general (Payne & Pereira, 2016).…”
Section: Criminal Prosecutionsmentioning
confidence: 99%